Antioxidative Activities of Essential Oils and Ethanol Extrations from Ornamental Zingiberaceae Species. Issue 1 (2nd January 2017) - Zhao, Mincong; Zhang, Lanyue; Yang, Zhiwen; Wei, Jingwen; Zhang, Kun; Zheng, Xi; Fang, Yanxiong; Lin, Li; Tang, Jian; Wu, Fengjuan; Du, Zhiyun
Abstract: The essential oils from five different Zingiberaceae species [ Costus speciosus (J. Konig.) Smith, Hedychium coronarium J. Koenig, Hedychium gardnerianum Griff., Zingiber zerumbet (Linn.) Roscoe ex Smith, Hedychium chrysoleucum Hook.] were extracted through hydro-distillation process and their chemical compounds were analyzed by GC-MS. In addition, the antioxidant activities of essential oils and ethanol extractions were described. The yields of essential oils ranged from 0.20 % in C. speciosus to 1.52 % in Z. zerumbet . A total of 48 components were identified, of which majority were ⟨-santalo (0.22-41.83 %), aromadendrene oxide I (39.63-55.40 %) and zerumbone (1.67-84.07 %). The essential oils showed an effective DPPH scavenging activities with IC50 values ranging between 5.28 and 13.26 μg/mL. The result showed that the ethanol extractions had different DPPH scavenging (IC50, 0.94-9.92 μg/mL) and most of them were lower than ascorbic acid (IC50, 8.37 μg/mL) and trolox (IC50, 10.19 μg/mL). The results indicate that the essential oils and ethanol extractions from the five ornamental Zingiberaceae species could serve as an important bio-resource of antioxidant for using in the functional food, cosmetic, and pharmaceutical industries.